Rancang Bangun dan Analisis Mesin Perajang Tembakau Menggunakan Mekanisme Poros Engkol - Alfauzi, Abdul Syukur; Janitra, Atikah Ayu; Setyo, Aan (Politeknik Negeri Semarang, 2023)
Tobacco is the main raw material that is utilized to make smoke. In the process the tobacco must experiences about carve, so that the process is then required carve engine existing chopper machine that uses the engine chopper blades involute results obtained in the chopped tobacco patches that appear black spots when dried so that we modify cutting mechanism carve crankshaft engine driving source motors 5.5 ( PK ) , and has been using the automated system on the conveyor secure in its use . In the selection of assessors and alternative design considerations needed to get the best design that later developed in the direction of making tools. This machine uses the calculation of motor power , the power distribution calculation , calculation , calculation of belt pulley diameter , shaft calculations . This machine has a design dimensions 1200 x 450 x 1050 ( mm ) with the results of chopped tobacco have uniformity chopped 2 , 4 and 6 ( mm )